Identification and comparison of three carp fishes based on mitochondrial 16S rRNA gene (Dhaka University Journal of Biological Sciences, 2017)
Identification of Labeo rohita, L. bata and L. gonius is sometimes problematic when usual morphological features are lost and it is difficult to differentiate them with traditional morphological features at their diverse developmental stages. PCR-sequencing provides an authentic alternative means of identification of individuals at species level. Three local carp fishes were collected and 16S rRNA genes were sequenced by sanger sequencing method after PCR amplification using universal primers. Obtained sequences were found accurate with blast search result which showed maximum range of similarity with the existing respective gene fragments present in GenBank database. Sequences were compared and multiple sequence alignment has revealed some polymorphic sites which can be used to differentiate these three species from one another. This study may provide valuable understanding to study their population in future.Dhaka Univ. J. Biol. Sci. 26(2): 167-174, 2017 (July)